Temimi and Ansari method for solving quadratic Riccati differential equation / Mat Salim Selamat ... [et al.] - Selamat, Mat Salim; Tajudin, Nurul Syafiqah; Roslan, Wahyu Hidayah; Rosli, Nur Aqilah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In this study, a quadratic Riccati equation is solved by using the Temimi and Ansari method (TAM)(Temimi and Ansari, 2011). The Riccati equation is a class of nonlinear differential equation and play important role in various fields in sciences and engineering. TAM was applied to solve a quadratic Riccati equation. The accuracy analysis show that TAM has a potential as a tool to solve the nonlinear differential equation